Variability in seasonal forecast skill of Northern Hemisphere winters over the twentieth century. Issue 11 (12th June 2017) - O'Reilly, Christopher H.; Heatley, James; MacLeod, Dave; Weisheimer, Antje; Palmer, Tim N.; Schaller, Nathalie; Woollings, Tim
Abstract: Seasonal hindcast experiments, using prescribed sea surface temperatures (SSTs), are analyzed for Northern Hemisphere winters from 1900 to 2010. Ensemble mean Pacific/North American index (PNA) skill varies dramatically, dropping toward zero during the mid‐twentieth century, with similar variability in North Atlantic Oscillation (NAO) hindcast skill. The PNA skill closely follows the correlation between the observed PNA index and tropical Pacific SST anomalies. During the mid‐century period the PNA and NAO hindcast errors are closely related. The drop in PNA predictability is due to mid‐century negative PNA events, which were not forced in a predictable manner by tropical Pacific SST anomalies. Overall, negative PNA events are less predictable and seem likely to arise more from internal atmospheric variability than positive PNA events. Our results suggest that seasonal forecasting systems assessed over the recent 30 year period may be less skillful in periods, such as the mid‐twentieth century, with relatively weak forcing from tropical Pacific SST anomalies. Key Points: PNA and NAO hindcast skill show marked variability over the twentieth century, following the varying link between tropical Pacific SST and the PNA Variability in PNA and NAO skill is linked on interannual time scales, notably during the mid‐century when the hindcast skill drops PNA‐ is less predictable, arising more from atmospheric variability; PNA+ is more clearly forced by warm tropical Pacific SST anomalies